Space Education and Awareness Activities in Nepal - Adhikary, Krishna Raj (Journal on Geoinformatics, Nepal, 2007)
The advancement in space technology has presented the modern world with many opportunities for collection, analysis and dissemination of information. The information of space technology could be used on various activities of development projects for economic growth and sustainable development of any country. In Nepal, the use and application of space technology has been brought into practice since 1970's. Government of Nepal has given the priority for the application of space technology to fulfill the national objective of poverty reduction and sustainable development of the country. This paper describes the various organizations involved on the application of space technology together with the space education and awareness activities in Nepal. Finally, it describes about the constraints and future prospectus of space technology application in Nepal.